PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA MELALUI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL - Ekawaty, Nurtista; Ronny, Ronny; Julianti, Emma (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
This research aims to examine the relationship between transformational leadership style and organizational culture on employee performance with job satisfaction as a mediating variable and organizational commitment as a moderating variable in millennial employees at the Financial Services Authority Office. The population in this study were employees of the East Java Province Financial Services Authority generation Y (millennials) who were born in 198-1994. Data collection techniques using questionnaires and analyzed using Partial Least Square (PLS). The results of the research show that Transformational Leadership Style has no significant effect on employee performance, Organizational Culture has a significant positive effect on employee performance, Transformational Leadership Style has a significant positive effect on job satisfaction, Organizational Culture has a significant positive effect on job satisfaction showing significant positive results, Job satisfaction has a significant effect significantly positive towards employee performance, Job satisfaction plays a mediating role in the influence of Transformational Leadership Style on employee performance, Job satisfaction plays a mediating role in the influence of organizational culture on employee performance,Organizational commitment plays a moderating role in the influence of Transformational Leadership Style on employee performance. Organizational Commitment plays a moderating role in the influence of organizational culture on employee performance.